EVALUASI INTERAKSI OBAT-OBAT PADA PASIEN DEWASA DI APOTEK PESISIR SURABAYA - Faizah, Ana Khusnul (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2022)
The pharmacist's responsibility is to prevent, find, and give solutions to drug interactions received by patients. Drug interactions could increase the effectiveness of therapy but can also have undesirable effects on toxicity. This study aimed to examine the potential drug-drug interactions in the prescriptions of adult patients at the Surabaya coastal pharmacy. This study was conducted with a retrospective method for three months at five pharmacies in the coastal area of Surabaya. We obtained 249 prescriptions and identified 85 (34%) that have potential drug-drug interactions. Among the 153 identified pDDIs, 0.7%, 18.3% and 35.5% were contraindicated, major and moderate severity types, respectively. Based on the mechanical action of drug interactions, 130 (84.9%) are identified by pharmacokinetics, 21 (13.7%) pharmacodynamics, and 2 (1.3%) unknowns. The pharmacist's role in providing safe, effective, and rational drug therapy can be done by either identifying drug interactions or preventing and minimizing the negative effect of drug interactions